2018
DOI: 10.1108/intr-05-2017-0203
|View full text |Cite
|
Sign up to set email alerts
|

Silver lining of envy on social media? The relationships between post content, envy type, and purchase intentions

Abstract: Purpose The purpose of this paper is to explore the prevalence of benign and malicious envy on social media, and to examine the relationships between shared content (experiential vs material purchases), envy type (benign vs malicious), and purchase intention (toward the same vs a superior object). Design/methodology/approach Three studies (N=622) were conducted to ask participants to recall the last time they experienced envy due to browsing social media, report an envy-triggering post about either an experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 60 publications
2
46
0
Order By: Relevance
“…Recently, R. Y. Lin (2018) discovered that consumers who feel benign envy are more likely to buy the same object possessed by their SNS friends. Similarly, Meier and Schäfer (2018) found that benign envy elicited in response to social comparison on Instagram leads to inspiration.…”
Section: The Mediating Role Of Benign Envy In Upward Social Comparisonmentioning
confidence: 99%
“…Recently, R. Y. Lin (2018) discovered that consumers who feel benign envy are more likely to buy the same object possessed by their SNS friends. Similarly, Meier and Schäfer (2018) found that benign envy elicited in response to social comparison on Instagram leads to inspiration.…”
Section: The Mediating Role Of Benign Envy In Upward Social Comparisonmentioning
confidence: 99%
“…For example, Carter and Gilovich (2010) claimed that material purchases are more comparable and thus more likely to trigger jealousy than experiential purchases. Lin (2018) also documented experiential purchases are more likely to trigger benign envy than material purchases and beneficial to the purchase intention of the envied object. Addressed to the stream of research on experiential purchases associated with negative emotion, our finding provides new strategies on how to cope with the negative impact of loneliness.…”
Section: Discussionmentioning
confidence: 94%
“…However, experiential purchases may also serve an important role for negative emotions. Lin (2018) found that experiential purchases and phrasing were less likely to be perceived as showing off on social media and thus may triggered more benign envy (motivates individuals to improve themselves and achieve the same success as others) than malicious envy (harm and belittling others and leads to negative social comparisons). Rosenzweig and Gilovich (2012) claimed that experiential purchase decisions are more likely to lead to regrets of inaction (missed opportunities that could have been done but was not), while material purchase decisions are more likely to generate regrets of action (remorse of a buyer that has not been done, but has done).…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…Glamorous photos of celebgrams posted on the Instagram tend to be more powerful in triggering follower envy . Furthermore, and Jin and Ryu (2020) state that celebgram trustworthiness as seen in Instagram photos is stronger narcissistically in generating consumer jealousy or envy and capable of leading to envy which in turn increases purchase intention (Lin, 2018).…”
Section: Effects Of Celebgram Trustworthinessmentioning
confidence: 99%
“…Theoretically, envy has a positive relationship with consumer purchase intention and tends to compete evolutionarily either intraexually or intersexually (Buunk & Massar, 2012). In the context of celebgram influencer-based marketing, narcissistic and glamorous photos can evoke envy and in turn increase consumer purchase intention (Milovic, 2014;Lin, 2018). Based on these theoretical and empirical reasons, the following hypothesis is proposed: H5: Possession envy has a positive effect on consumer purchase intention.…”
Section: Possession Envymentioning
confidence: 99%